Sentinel lymph node detection for lung cancer surgery: a possible pathological surrogate of overall lymph node dissection - Stasiak, Florent; Seitlinger, Joseph; Walsh, Lyndon C.; Streit, Arthur; Siat, Joelle; Gauchotte, Guillaume; Schnedecker, Lucie; Renaud, Stéphane (Frontiers in Oncology, 2025)
BackgroundSystematic lymph node dissection (SLND) is currently the gold standard for lung cancer surgery. However, this is not the case for breast cancer or melanoma, where sentinel lymph node (SLN) identification is routine. The SLN could be a possible surrogate for the pathological status of the other lymph nodes, but there is limited data in the literature for lung cancer surgery. The main objective of this study was to evaluate pathological concordance between the SLN and the complete lymphadenectomy.MethodsIn this retrospective study, we reviewed all cases of localized lung cancer that had benefited from our SLN identification protocol and underwent surgery (segmentectomy or lobectomy) between December 2020 and December 2023. We examined the pathological status of the SLN and the rest of the lymph node dissection to assess the pathological concordance rate.ResultsAfter exclusion, 106 patients with localized stage I-IIA non-small cell lung cancer and suspected node negative disease (N0) were included in our study. Of these 106 patients, 96 had a pN0 SLN (90.6%) and 10 had a positive SLN (pN+), resulting in an upstaging rate of 9.4%. All patients with a pN0 SLN were also pN0 for the rest of the lymph node dissection, corresponding to a pathological concordance rate of 100%. Disease-free survival was statistically lower in the pN+ SLN group than in the pN0 SLN group (p<0.0001).ConclusionWe demonstrated a 100% pathological concordance between SLN when it is cancer-free and the rest of the lymph nodes in the lymph node dissection, suggesting that the SLN is a good indicator of the overall pathological status of the other lymph nodes in the thorax.